(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To identify some factors related to acne in students of Nam Dan 1 High School, Nghe An Province in 2025. Subjects and methods: This cross-sectional descriptive study involved 333 students at Nam Dan 1 High School, Van An commune, Nghe An province, from December 2024 to September 2025. Data were collected using an Acne Status Assessment Form completed by dermatologists after observation, and related factors were collected using a pre-designed questionnaire. Results and Conclusions: Of the 333 students participating in the study, the proportion of female students was higher than that of male students. A statistically significant association was found between family history of acne, dietary habits, and acne in students (p<0.05). A statistically significant association was also found between the use of cosmetics and the habit of picking at pimples and acne in students.